Comment devient-on aborigène? trajectoires familiales dans le Sud-Est de l’Australie (2009)
This article presents the life-story of an Australian Indigenous man named Albert Widders. His story is revealing as his life seems to have been cut in two by the emergence of a segregated order in the South-East of Australia. Born in the 1840s, he was well integrated into settler society in the first part of his life, even marrying a European woman. Yet, after the breaking-up of his marriage, Albert moved to a new region and formed a new family, this time with an Aboriginal woman. From those two marriages came two families, one living in the Aboriginal world, the other in the Euro-Australian world. Albert’s life and the contrasting trajectories of his two families give us new insights into the shifting racial relations in South-East Australia and the hardening, in the 20th century, of the dichotomy between ‘black’ and ‘white’.